The Association between Maternal Knowledge, Family Support, and Exclusive Breastfeeding in Siborong Borong Community Health Center, North Tapanuli, North Sumatera - Sipahutar, Selferida; Lubis, Namora Lumongga; Siregar, Fazidah Agusliana (Journal of Maternal and Child Health, 2019)
Background: Exclusive breastfeeding means that the infant receives only breast milk. No other liquids or solids are given – not even water – with the exception of oral rehydration solution, or drops/syrups of vitamins, minerals or medicines.WHO reported that nearly 90% of the under-five deaths occurred in developing countries and more than 40% of the deaths were due to diarrhea and acute respiratory infections. These diseases can be prevented by exclusive breastfeeding. This study aimed to examine the association between maternal knowledge, family support and exclusive breastfeeding in SiborongBorong Community Health Center, North Tapanuli, North Sumatera.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted at Siborongborong community health center, North Tapanuli, North Sumatera. A sample of 97 mothers who had children aged 6-12 months were selected for this study by proportional random sampling. The dependent variable was exclusive breastfeeding. The independent variables were maternal knowledge and family support. The data were analyzed by simple logistic regression.Results: Exclusive breastfeeding was associated with maternal knowledge (OR=11.40; p= 0.001) and family support (OR= 9.30; p= 0.001).Conclusion: Exclusive breastfeeding is associated with maternal knowledge and family support.Keywords: exclusive breastfeeding, maternal education, family supportCorrespondence: Selferida Sipahutar. Masters Program in Public Health, Faculty of Public Health, Universitas Sumatera Utara, Jl. Universitas 21, Medan 20115, North Sumatera, Indonesia. Email: selferidabidan@gmail.com. Mobile: +081362123930Journal of Maternal and Child Health (2019), 4(5): 338-341https://doi.org/10.26911/thejmch.2019.04.05.06